Obesity indices comparison and its correlation with random blood sugar and blood pressure in adults in rural field practice area of a medical college - Mendhe, Harshal Gajanan; Narni, Hanumanth; P., Satyanarayana Chowdary; M., Shashikanth (International Journal Of Community Medicine And Public Health, 2016)
Background: The prevalence of obesity has doubled in adults and children and tripled in adolescents over the past 2 decades. Body Mass Index (BMI) has gained international acceptance as a standard for recognition and classification of overweight and obesity. Measuring Waist Circumference (WC) alone is a simpler way of assessing for abdominal fat and has been shown by more recent research to be superior to WHR in determining health risks. This present study was conducted among the adults above 30 years adults in the rural field practice area of a medical college with the objectives to assess prevalence of obesity using BMI, WC, WHR and WHtR, to compare these indices and to correlate obesity indices with random blood sugar level and blood pressure. Methods: It was a household survey in which 1150 participants were included as study subjects. Results: It was observed that 16.8% study participants were obese as per International classification of BMI, 35% study participants were obese as per BMI National classification and WHR, 26.7% were obese as per WC classification and 66% study participants were obese as per WHtR. In the present study, it was observed that none of the obesity indices was found to be correlated with Systolic B.P, Diastolic B.P and Random blood sugar level. Conclusions: WHtR greater than 0.5 is a simple and effective indicator of centralized obesity. It measures obesity in those individuals which are healthy according to BMI and WC. One can use a simple instrument such as measuring tape to assess obesity as it measures WC, WHtR, and WHR instead of using heavy and non-calibrated weighing machine.